The study of African traditional religion and its challenges in contemporary times - Omotoye, Rotimi W. (Ilorin Journal of Religious Studies, 2011)
African Traditional Religion is the traditional religion of the African people before the coming of Islam and Christianity. However, the missionaries of the two foreign religions succeeded in converting some African people to the new religions. The African religion was condemned by the Early European scholars, travelers, investigators and missionaries. The educated Elite who were products of the schools established by the Christian missionaries in particular and the converts in general did not see anything good in African religion. It is interesting to note that African traditional religion is being studied in many Universities and Colleges in Africa since the beginning of the 20th century, so that it may not go into total neglect in African history and culture. The study, therefore, is facing many challenges which are affecting the interest of African scholars in the field. The paper has been able to highlight the problems of African religion in the contemporary time, while some suggestions are given, so as to make it meet the challenges of the modern times.
free
Keywords: Africa – Education; Africa – Religion; Christianity and African religions; Indigenous peoples – Africa; Islam and African religions; Religion – History – Study and teaching; Religion – Study and teaching; Universities and colleges – Africa; Yoruba (African people) – Religion